The Correlation Between Dietary Calcium Intake and Bone Mineral Density in Postmenopausal Women - L. Cerrahoğlu; Mehmet Tuncay Duruöz; C. Tıkız; S. Ölçenler; N. Tulukoğlu; A. Süsin (Türk Osteoporoz Dergisi, 2002)
The present study was performed to assess the relation between dietary calcium intake and bone mineral density in postmenopausal women. For this purpose 87 postmenopausal who had not got any treatment that interacts with bone metabolism previously were enrolled in the study. The standard questionnaire was filled out by a physician to determine the daily calcium intake for each patient. Bone mineral density T and Z scores of L1-L4 region, L3 lateral, femur neck, trochanter and Ward’s triangle were assessed. Spearman’s nonparametric rank correlation coefficient was used to evaluate the relation between two quantitative variables. In conclusion; only a close relationship was observed between the dietary calcium intake and the bone mass index and Z-score in L1-L4 region (r= 0.521, p=0.015; r=0.482, p=0.027, respectively). No relationship was found between the bone mass index Z and T-score and the dietary calcium intake in remaining four regions.